2020
DOI: 10.1088/1742-6596/1470/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of teacher’s teaching skills and students’ intrapersonal intelligence toward metacognitive awareness of students in state vocational school in Blitar

Abstract: Vocational High School graduates who can study independently will become lifelong learners who are responsive to change so they can compete in the workforce of the revolutionary era 4.0. But the learning process at Vocational High School is still not paying attention to the development of high-level thinking skills of students. This is in line with the opinion of Mukhadis that the implementation of learning in the field of technology is still less encouraging which has an impact on the lack of development of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Maryati et al found a strong association between the intrapersonal intelligence teaching model and students' metacognitive capacities in their research of the correlation between teacher's teaching skills and intrapersonal intelligence on students' metacognitive awareness at SMKN Blitar City (Maryati, Khasanah, & Maf'ula, 2020).…”
Section: Metacognitive To Intrapersonal Intelligencementioning
confidence: 99%
“…Maryati et al found a strong association between the intrapersonal intelligence teaching model and students' metacognitive capacities in their research of the correlation between teacher's teaching skills and intrapersonal intelligence on students' metacognitive awareness at SMKN Blitar City (Maryati, Khasanah, & Maf'ula, 2020).…”
Section: Metacognitive To Intrapersonal Intelligencementioning
confidence: 99%